2014
DOI: 10.4101/jvwr.v7i3.7036
|View full text |Cite
|
Sign up to set email alerts
|

Meta-theoretic Assumptions and Bibliometric Evidence Assessment on 3-D Virtual Worlds as Collaborative Learning Ecosystems

Abstract: Computer-supported online 3-D virtual world environments have been waxed and waned in interest and representativeness for supporting collaborative-and simulation-based practices. In a postmodern societal framework that requires inexpensive solutions for high-risk situations, research efforts in virtual worlds have developed a basis for understanding the use of virtual reality for multidisciplinary scenarios such as distance learning, training, therapy treatment, and social interaction. Complex relationships ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Their study found that articles originating from Mainland China elicited the most citations, followed by those from Taiwan, Hong Kong, and Macau, respectively. Other contemporary bibliometrics research has examined a variety of topics such as social capital (Chul-joo & Dongyoung, 2016), virtual media (Correia et al, 2014), video gaming (White, 2011), and gender and media (Navarro & Martín, 2013).…”
Section: Citation Analysis In Communication Researchmentioning
confidence: 99%
“…Their study found that articles originating from Mainland China elicited the most citations, followed by those from Taiwan, Hong Kong, and Macau, respectively. Other contemporary bibliometrics research has examined a variety of topics such as social capital (Chul-joo & Dongyoung, 2016), virtual media (Correia et al, 2014), video gaming (White, 2011), and gender and media (Navarro & Martín, 2013).…”
Section: Citation Analysis In Communication Researchmentioning
confidence: 99%
“…The details about the initial sample selection and review processes were presented by Correia et al (2014), and this chapter extends the previous work by distilling conceptual evidences as meta-theoretic units of analysis. The results of this study were obtained applying a Systematic Literature Review (SLR) process based on the known guidelines (Kitchenham et al, 2009;Stapić et al, 2012).…”
Section: Methodsmentioning
confidence: 69%